Handbook for III-V high electron mobility transistor technologies - Nirmal, D.; Ajayan, J. (Boca Raton, FL : CRC Press, 2019)
This book focusses on III-V high electron mobility transistors (HEMTs) including basic physics, material used, fabrications details, modeling, simulation, and other important aspects. It initiates by describing principle of operation, material systems and material technologies followed by description of the structure, I-V characteristics, modeling of DC and RF parameters of AlGaN/GaN HEMTs. The book also provides information about source/drain engineering, gate engineering and channel engineering techniques used to improve the DC-RF and breakdown performance of HEMTs. Finally, the book also highlights the importance of metal oxide semiconductor high electron mobility transistors (MOS-HEMT). Key Features Combines III-As/P/N HEMTs with reliability and current status in single volume Includes AC/DC modelling and (sub)millimeter wave devices with reliability analysis Covers all theoretical and experimental aspects of HEMTs Discusses AlGaN/GaN transistors Presents DC, RF and breakdown characteristics of HEMTs on various material systems using graphs and plots
1. Motivation Behind High Electron Mobility Transistors [Mayank Chakraverty] 2. Introduction to High Electron Mobility Transistors [Rama Komaragiri] 3. HEMT Material Technology and Epitaxial Deposition Techniques [Rama Komaragiri] 4. Source/Drain, Gate and Channel Engineering in HEMTs [Palash Das, T. R. Lenka, Satya Sopan Mahato, and A. K. Panda] 5. AlGaN/GaN HEMTs for High Power Applications [P. Prajoon and Anuja Menokey] 6. AlGaN/GaN HEMT Fabrication and Challenges [Gourab Dutta, Srikanth Kanaga, Nandita DasGupta, and Amitava DasGupta] 7. Analytical Modeling of High Electron Mobility Transistors [N. B. Balamurugan] 8. Polarization Effects in AlGaN/GaN HEMTs [Palash Das, T. R. Lenka, Satya Sopan Mahato, and A. K. Panda] 9. Current Collapse in AlGaN/GaN HEMTs [Sneha Kabra and Mridula Gupta] 10. AlGaN/GaN HEMT Modeling and Simulation [Binit Syamal and Atanu Kundu] 11. Breakdown Voltage Improvement Techniques in AlGaN/GaN HEMTs [Vimala Palanichamy] 12. InP/InAlAs/InGaAs HEMTs for High Speed and Low Power Applications [Nilesh Kumar Jaiswal and V. N. Ramakrishnan] 13. A Study of the Elemental and Surface Characterization of AlGaN/GaN HEMT by Magnetron Sputtering System [Roman Garcia-Perez, Karen Lozano, Jorge Castillo, and Hasina F. Huq] 14. Metamorphic HEMTs for Sub Millimeter Wave Applications [J. Ajayan and D. Nirmal] 15. Metal Oxide Semiconductor High Electron Mobility Transistors [D. K. Panda, G. Amarnath, and T. R. Lenka] 16. Double Gate High Electron Mobility Transistors [Ajith Ravindran]
OCLC-licensed vendor bibliographic record.
Keywords: Modulation-doped field-effect transistors -- Handbooks, manuals, etc; SCIENCE / Physics; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / Circuits / General; TECHNOLOGY & ENGINEERING / Mechanical